Report From the 6th International Meeting on Bone Marrow Adiposity (BMA2020) - Scheller, Erica L.; McGee-Lawrence, Meghan E.; Lecka-Czernik, Beata (Frontiers in Endocrinology, 2021)
The 6th International Meeting on Bone Marrow Adiposity (BMA) entitled “Marrow Adiposity: Bone, Aging, and Beyond” (BMA2020) was held virtually on September 9th and 10th, 2020. The mission of this meeting was to facilitate communication and collaboration among scientists from around the world who are interested in different aspects of bone marrow adiposity in health and disease. The BMA2020 meeting brought together 198 attendees from diverse research and clinical backgrounds spanning fields including bone biology, endocrinology, stem cell biology, metabolism, oncology, aging, and hematopoiesis. The congress featured an invited keynote address by Ormond MacDougald and ten invited speakers, in addition to 20 short talks, 35 posters, and several training and networking sessions. This report summarizes and highlights the scientific content of the meeting and the progress of the working groups of the BMA society (http://bma-society.org/).